A Pocket Guide to the US Constitution : What Every American Needs to Know, Second Edition - Arnold, Andrew Bernard (Georgetown University Press, 2018)
This handy guide helps readers understand, quickly and in nontechnical language, the US Constitution. Want to learn about the separation of powers, the emoluments clause, why slaves in colonial America were considered 3/5 of a person, gerrymandering, or why Congressional pay raises are limited? Historian Andrew Arnold provides a simple, non-partisan, line-by-line commentary with concise explanations of the Constitution's meaning and history, offering little known facts and anecdotes about all twenty-seven amendments, and discusses key Supreme Court cases through the ages. For ease of use Arnold follows the actual numbering system of articles, sections, and clauses in the Constitution. The book includes two tables of contents--one brief and one detailed--as well as a bibliography and a short conclusion by Arnold on the enduring significance of the Constitution.